Grazing-incidence scattering—status and perspectives in soft matter and biophysics. (August 2019) - Jaksch, Sebastian; Gutberlet, Thomas; Müller-Buschbaum, Peter
Abstract: Investigating lateral structures of surfaces and interfaces from the mesoscale down to atomic resolution is of growing interest to modify, functionalize, and understand the behavior of materials in soft matter and biophysics. Grazing-incidence scattering techniques have proven to be very powerful for such kind of studies. Using X-rays and neutrons also buried lateral structures can be accessed in a non-destructive way. The large probed sample area provides a high statistical relevance of the determined structure information, and complex sample environments in combination with in situ and in operando experiments provide the full potential for gaining deep insights in structure formation processes. In the brief review, we reflect on the current state of the art of grazing-incidence scattering techniques using X-rays and neutrons, fields of interest, and applications in soft matter and biophysics, resulting in challenges and providing a short outlook. Owing to the already available literature on X-ray–based techniques, we will set a slight emphasis on neutron-based techniques. Graphical abstract: Investigating lateral structures of surfaces and interfaces from the mesoscale down to atomic resolution is of growing interest to modify, functionalize, and understand the behavior of materials in soft matter and biophysics. Grazing-incidence scattering (GIS) techniques have proven to be very powerful for such kind of studies. Using X-rays and neutrons also buried lateral structures can be accessed in a non-destructive way. The large probed sample area provides a high statistical relevance of the determined structure information and complex sample environments in combination with in-situ and in-operando experiments provide the full potential for gaining deep in-insights in structure formation processes. In the brief review we reflect on the current state of the art of GIS techniques using X-rays and neutrons, fields of interest and applications in soft matter and biophysics, resulting challenges and provide a short outlook. Due to the already available literature on X-ray based techniques we will set a slight emphasis on neutron based techniques.Image 1